Automation of IoT-Based Microclimate Management for Traditional Medicinal Plant Cultivation as a Catalyst for Sustainable Development in the North Sulawesi Community (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program implements an IoT-based automation system for environmental management in the cultivation of bio-pharmaceutical plants in North Sulawesi, adopting a Community-Based Participatory Research (CBPR) approach. Utilizing the CBPR method, all program stages were designed and executed participatorily with three farmer groups involving 9 community members over six months, encompassing problem identification, system design, installation, monitoring, and evaluation. The system implementation involved the installation of DHT11 sensors, NodeMCU ESP8266 modules, and actuators, all integrated with a cloud platform. Test results demonstrated that the system successfully stabilized the cultivation environment with high consistency, maintaining temperature at 26±1°C and humidity at 50±5%, compared to pre-intervention conditions (temperature: 23-34°C, humidity: 30-70%). These optimal conditions significantly enhanced harvest quality, evidenced by a 10% increase in average harvest weight compared to conventional cultivation methods. The active participation of the community throughout the process not only ensures the system's sustainability but also strengthens the community's technological capacity.